Bioleaching assisted foam fractionation for recovery of gold from the printed circuit boards of discarded cellphone. (1st January 2020) - Zhou, Gang; Zhang, Huixin; Yang, Wei; Wu, Zhaoliang; Liu, Wei; Yang, Chunyan
Graphical abstract: Highlights: An effective strategy for the recovery of Au from the WPCBs was proposed. Two cyanide-producing microorganisms were co-cultured. A novel internal component of VSTC was developed. Foam fractionation was used to concentrate Au by using CTAB as the collector. Abstract: Present work was focused on recovering gold (Au) from the printed circuit boards (PCBs) of discarded cellphone by bioleaching assisted continuous foam fractionation. First, the cyanide-producing strains of Pseudomonas putida and Bacillus megaterium were co-cultured in order to supply a high cyanide concentration in the nutrient solution for mobilizing Au from waste PCBs (WPCBs). Bioleaching conditions were optimized by using response surface methodology. Under the suitable bioleaching conditions of pH of 10.0, pulp density of 5 g/L and leaching time of 34 h, the Au mobilization percentage was 83.59%. The leaching liquor with an Au concentration of 1.34 mg/L could be used as the feeding solution of continuous foam fractionation after removing solid particles and cell biomass. In order to strengthen foam drainage, a novel internal component of foam fractionation column was developed. Under the suitable operation conditions of CTAB concentration of 0.2 g/L, volumetric air flow rate of 100 mL/min and feed flow rate of 10 mL/min, the enrichment ratio and recovery percentage of Au were 43.62 and 87.46%, respectively. This study is expected to provide an effective strategy to recover Au from WPCBs, and to supplement the depleting natural resources.